RETRACTED ARTICLE: A novel, bioactive and antibacterial scaffold based on functionalized graphene oxide with lignin, silk fibroin and ZnO nanoparticles - Reza Eivazzadeh-Keihan; Ensiye Zare-Bakheir; Hooman Aghamirza Moghim Aliabadi; Mostafa Ghafori Gorab; Hossein Ghafuri; Ali Maleki; Hamid Madanchi; Mohammad Mahdavi (Scientific Reports)
Abstract In this study, a novel nanobiocomposite was synthesized using graphene oxide, lignin, silk fibroin and ZnO and used in biological fields. To synthesize this structure, after preparing graphene oxide by the Hummer method, lignin, silk fibroin, and ZnO nanoparticles (NPs) were added to it, respectively. Also, ZnO NPs with a particle size of about 18 nm to 33 nm was synthesized via Camellia sinensis extract by green methodology. The synthesized structure was examined as anti-biofilm agent and it was observed that the Graphene oxide-lignin/silk fibroin/ZnO nanobiocomposite has a significant ability to prevent the formation of P. aeruginosa biofilm. In addition, due to the importance of the possibility of using this structure in biological environments, its toxicity and blood compatibility were also evaluated. According to the obtained results from MTT assay, the viability percentages of Hu02 cells treated with Graphene oxide-lignin/silk fibroin/ZnO nanobiocomposite after 24, 48, and 72 h of incubation were 89.96%, 89.32%, and 91.28%. On the other hand, the hemolysis percentage of the synthesized structure after 24 h and 72 h of extraction was 9.5% and 11.76% respectively. As a result, the synthesized structure has a hemolysis percentage below 12% and its toxicity effect on Hu02 cells is below 9%.